When life gives you pears eaudiobook The healing power of family, faith, and funny people. - Gaffigan, Jeannie (2019)
The Big Sick meets Dad is Fat in this funny and heartfelt New York Times bestselling memoir from writer, director, wife, and mother, Jeannie Gaffigan, as she reflects on the life-changing impact of her battle with a pear-sized brain tumor. In 2017, Jeannie's life came to a crashing halt when she was diagnosed with a life-threatening brain tumor. As the mother of 5 kids — 6 if you include her husband — sat in the neurosurgery department in star-covered sweats too whimsical for the seriousness of the situation, all she could think was "Am I going to die?" Thankfully, Jeannie and her family were able to survive their time of crisis, and now she is sharing her deeply personal journey through this miraculous story: the challenging conversations she had with her children; how she came to terms with feeling powerless and ferociously crabby while bedridden and unable to eat for a month; and how she ultimately learned, re-learned and re re-learned to be more present in life. With sincerity and hilarity, Jeannie invites you into her heart (and brain) during this trying time, emphasizing the importance of family, faith and humor as keys to her recovery and leading a more fulfilling life.